1967
DOI: 10.1029/jz072i005p01443
|View full text |Cite
|
Sign up to set email alerts
|

SporadicEand the wind structure of theEregion

Abstract: Observations of neutral winds from visible trails of gun‐launched vehicles and radio soundings of the ionospheric sporadic E layers are described and compared. It is shown that the wind structure accounts for many features of the sporadic E layer variation on two nights of observation, through the vertical ion convergence mechanism described most recently by MacLeod [1966]. Except for some transient disagreements, the sporadic E is found to accompany the height variation of certain levels of zero ion velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1968
1968
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…All three components of motion (x, y, z) interpreted as a background wind, will contribute through interaction with the inclined geomagnetic field to a vertical component of ion motion, V z . If the ionization flux due to V z converges at some altitude, a sporadic E-layer may form there in accord with recently developed theories of sporadic E [18], [19]. This is found to be the case in the present example.…”
Section: The L O N E S O N D Esupporting
confidence: 87%
“…All three components of motion (x, y, z) interpreted as a background wind, will contribute through interaction with the inclined geomagnetic field to a vertical component of ion motion, V z . If the ionization flux due to V z converges at some altitude, a sporadic E-layer may form there in accord with recently developed theories of sporadic E [18], [19]. This is found to be the case in the present example.…”
Section: The L O N E S O N D Esupporting
confidence: 87%
“…To date the wind-shear theory has been considered mainly in terms of quasi-steady conditions in which the wind profile does not vary with time. Observations of neutral winds, however, suggest that the profile of horizontal velocities descends with time [Revah and Spizzichino, 1966;Rosenburg and Justus, 1966;Wright et al, 1967]. This is consistent with the theory of internal gravity waves [Hines, 1960], which predicts that the phase velocity of the x Present address: Department of Physics, University of Toronto, Toronto 5, Canada.…”
Section: Introductionmentioning
confidence: 54%
“…The Whitehead-Storey theory of sporadic E formation through the wind-shear mechanism has been developed in considerable detail [e.g., see Whitehead, 1967; Ax•ord, l!J67] and found to account for much of the observed data [Wright et al, 1967;Aubry et al, 1966;MacLeod, 1966;Young et al, 1967]. However, it is commonly found that low-altitude (85-95 km) sporadic E layers occur at positions that do not have any clear relationship to simultaneously observed neutral wind profiles [Wright et al, 1967;Aubry et al, 1966;Mac-Leod, 1966], and indeed the layers often appear to be located in regions of ionization divergence, in direct contradiction to the usual predictions of the wind-shear theory.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the wind shear mechanism plays a major role in sporadic E layer formation (Whitehead, 1961(Whitehead, , 1989. According to this theory the sporadic E layer is created by the vertical compression of metal ions in a shear of the horizontal wind (Wright et al, 1967). Wind shears are provided by tidal waves producing a descending layer.…”
Section: Discussionmentioning
confidence: 99%